SYNTHESIS OF NANO-BENTONITE MODIFIED GRAPHENE OXIDE ELECTRODE FOR FORMALDEHYDE ANALYSIS BY CYCLIC VOLTAMMETRY - Setiarso, Pirim; Fajrin, Aisyah Rahmatul (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
In this research, each graphene oxide and nano-bentonite was synthesized using the Improved Hummers method and the Sonochemical method for formaldehyde detection by cyclic voltammetry. Formaldehyde detection by cyclic voltammetry has several factors to accurately detect formaldehyde, such as electrode composition, the pH of the solution, the deposition time, and the scan rate. In this study, formaldehyde detection using nano-bentonite modified graphene oxide electrode has the optimum electrode composition in the ratio of graphene oxide: paraffin: nano-bentonite 3:2:5, pH of the optimum solution for detection of formaldehyde 4, 10-second deposition time and scan rate 100 mV/sec. Nano-bentonite modified graphene oxide electrode has a detection limit of up to 0.16856 ppm (0.005613 mM) with a recovery of 99.414%. This sensor was successfully applied for formaldehyde measurement in the actual sample and showed good selectivity, sensitivity, reproducibility, and precision.